Roman Britain - Salway, Peter (Oxford University Press, 2000)
Peter Salway's Very Short Introduction to Roman Britain weaves together the results of archaeological investigation and historical scholarship in a rounded and highly readable concise account. He charts life in Roman Britain from the first Roman invasion under Julius Caesar to the final collapse of the Roman Empire in the West around AD 500